Methods to facilitate learning processes in different educational contexts - Monica Fedeli; Daniela Frison (Firenze University Press, 2018)
The purpose of this paper is to explore the facilitation process of learning and teaching in a university bachelor's degree program L-19 for educators and trainers in Italy. Facilitation is seen as a participatory student-centered teaching approach to promote interactive methods among students. The paper begins by describing participatory methods and strategies and related challenges concerning the professional work of the educator-trainer. The second part of the paper describes the implications that such methods have in practical educational and training contexts. The paper concludes with a discussion about the learning outcomes based on the context in which the educator-trainer is called to act professionally. The paper directs the educators and faculty towards a constructive alignment of the teaching methods and assessment strategies for the achievement of greater learning outcomes.   Metodi per la facilitazione dei processi di apprendimento nei diversi contesti educativi Il presente contributo affronta il tema della facilitazione dei processi di apprendimento e insegnamento con particolare riferimento alla classe di laurea L-19. La facilitazione è considerata un approccio learner-centered che promuove metodi partecipativi e interattivi che riguardano l'agire professionale dell'educatore-formatore. Nella seconda parte del contributo si descrivono le implicazioni che tali metodi hanno nell'applicazione in contesti educativi e formativi. Il contributo conclude con una discussione sui risultati di apprendimento declinati sulla base del contesto e del target rispetto al processo di facilitazione su cui l'educatore-formatore è chiamato ad agire professionalmente. La definizione dei risultati di apprendimento orienta il docente verso l'allineamento costruttivo dei metodi didattici e delle strategie di facilitazione e di valutazione per il migliore raggiungimento dei learning outcomes.